The Effect of Tax Aggressiveness, Return On Assets, Leverage and Size on Corporate Social Responsibility (Empirical Study on Manufacturing Companies Listed on the Indonesia Stock Exchange 2015-2019 Period) - Maria G. I. D. Sarmento (Jurnal Riset Perpajakan: Amnesty, 2022)
The Purpose of this study is to analyze the effect of tax agrrissiveness, return on assets, leverage adn size on corporate social responsibility (CSR). This study uses the independent tax agressiveness with ETR (Effective Tax Rates), Return On Assets (ROA), Leverage and size while the dependent variable in this study is orporate Social Responsibility (CSR). The population on this study was manufaturing companies listed on Indonesia Stick Exchange. Sample were taken by purposive sampling method. The total sample for this study is 76 samples tkane from 20 companies. Data where analyzed using ordinary least square regression, analysis model with the help of software SPSS25. The result of this study idicate that the independent variable tax agressiveness , ROA and leverage have significant possitive effect on CSR, while size  has no effect on CSR